2012
DOI: 10.4315/0362-028x.jfp-11-276
|View full text |Cite
|
Sign up to set email alerts
|

Antimicrobial Effects of Silver Nanoparticles against Bacterial Cells Adhered to Stainless Steel Surfaces

Abstract: Given the increasing number of antibiotic-resistant bacteria and the need to synthesize new antimicrobials, silver has attracted interest in the scientific community because of its recognized antimicrobial activity. This study aimed to evaluate the antimicrobial effects of silver nanoparticles (NP) obtained by a new method and tested at concentrations of 6 μg/ml and 60 μg/ml against the species Staphylococcus aureus, Listeria innocua, Salmonella Choleraesuis, Pseudomonas aeruginosa, Escherichia coli, and Baci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(18 citation statements)
references
References 12 publications
0
17
0
1
Order By: Relevance
“…We chose silver as the initial source material for HMs because of the growing research literature on the potential clinical utility of engineered silver nanoparticles for cancer and infectious disease treatment [20,[44][45][46][47][48][49][50]. Silver has good optical contrast properties for visualization in TEM, NTA, and other NP characterization technologies and a welldescribed UV-vis wavelength range, including red-shift of silver surface plasmon resonance peaks from interactions with silica [51,52] Prior infrared and Raman spectroscopy and photoluminescence studies on homeopathically-prepared medicines have shown that the material retains a spectroscopic [34,53,54] and photonic [28][29][30] "signature" of the original source material.…”
Section: Methodsmentioning
confidence: 99%
“…We chose silver as the initial source material for HMs because of the growing research literature on the potential clinical utility of engineered silver nanoparticles for cancer and infectious disease treatment [20,[44][45][46][47][48][49][50]. Silver has good optical contrast properties for visualization in TEM, NTA, and other NP characterization technologies and a welldescribed UV-vis wavelength range, including red-shift of silver surface plasmon resonance peaks from interactions with silica [51,52] Prior infrared and Raman spectroscopy and photoluminescence studies on homeopathically-prepared medicines have shown that the material retains a spectroscopic [34,53,54] and photonic [28][29][30] "signature" of the original source material.…”
Section: Methodsmentioning
confidence: 99%
“…Nanotechnology is one of the most attractive areas of research in modern material science due to their potential applications in numerous fields, including mechanics, biomedical, energy science, catalysis, optoelectronics, magnetics sciences, and sensors (Araujo et al 2012, Sulaiman et al 2013. Metal nanoparticles (MNPs) pave significance attraction of researchers because of their unique properties such as increased catalytic activity due to morphologies with highly active facets as compared to bulk material (Ahmed et al 2015).…”
Section: Introductionmentioning
confidence: 99%
“…34,137e140 Nanoparticles can adsorb onto stainless steel container surfaces as well. 141,142 However, if a manufacturer uses traditional methods to make their higher potency remedies, borosilicate glassware e and hence, silica e will likely be involved during succussion steps. 5 In contrast with conventional bulk form materials, smaller nanoscale structures, including nano-silica, acquire unusual electromagnetic, magnetic, optical, electronic, and quantum mechanical properties.…”
Section: Dilutionin Nanoscience: Possible Relevance Tohomeopathic Manmentioning
confidence: 99%